2011
DOI: 10.1364/oe.19.025570
|View full text |Cite
|
Sign up to set email alerts
|

Airy-soliton interactions in Kerr media

Abstract: We investigate and analyze temporal soliton interactions with a dispersive truncated Airy pulse traveling in a nonlinear fiber at the same center wavelength (or frequency), via split step Fourier numerical simulation. Truncated Airy pulses, which remain self-similar during propagation and have a ballistic trajectory in the retarded time frame, can interact with a nearby soliton by its accelerating wavefront property. We find by tracking the fundamental parameters of the emergent soliton-time position, amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…According to the nonlinear Schrödinger equation, the nonlinearity plays a nontrivial role in controlling the persistence as well as the breakdown of Airy beams [36][37][38]. It has been demonstrated that the main lobe of an Airy beam experiences self-phase modulation in NL media that results in the self-focusing or trapping of the beam [33]. And the field distribution of the Airy beam varies differently in different NL media [36,39].…”
Section: Introductionmentioning
confidence: 99%
“…According to the nonlinear Schrödinger equation, the nonlinearity plays a nontrivial role in controlling the persistence as well as the breakdown of Airy beams [36][37][38]. It has been demonstrated that the main lobe of an Airy beam experiences self-phase modulation in NL media that results in the self-focusing or trapping of the beam [33]. And the field distribution of the Airy beam varies differently in different NL media [36,39].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Ellenbogen et al produced an Airy beam in an asymmetrically modulated quadratic optical NL medium by the three-wave mixing process [25]. This novel nonlinear generation method not only produced an Airy beam at a new wavelength and a higher energy, but also provided new possibilities for manipulating the dynamics of Airy beams in NL media [26][27][28][29][30]. According to the nonlinear Schrödinger equation, the nonlinearity plays a nontrivial role in controlling the persistence as well as the breakdown of Airy beams [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…According to the nonlinear Schrödinger equation, the nonlinearity plays a nontrivial role in controlling the persistence as well as the breakdown of Airy beams [31][32][33]. It has been demonstrated that the main lobe of an Airy beam experiences self-phase modulation in NL media that results in the self-focusing or trapping of the beam [28]. At that, the field distribution of the Airy beam varies differently in different NL media [31,34].…”
Section: Introductionmentioning
confidence: 99%
“…In optics, Airy wave-packets were first introduced in the context of spatial optics Airy beams [2,3] , and the corresponding non-linear dynamics were presented in [4,5]. These ideas have also been applied in temporal optics, where the unique propagation properties of temporal Airy-based pulses has been recently investigated in both linear and non-linear media, namely in linear light bullets [6,7], soliton pulses generation [8], Airy-soliton interaction [9], supercontinuum generation [10], spectrum to distance mapping [11], linear dispersive invariant propagation by flat-topped spectrum Airy-based pulses [12,13], and linear dispersive attenuation invariant propagation by Airy-based "rocket" pulses [14]. In a similar way to optical solitons [15], optical Airy pulses exhibit temporal propagation invariance of the temporal intensity as it propagates through a linear dispersive media during a limited propagation path, until a "critical point" where the pulse breaks up [16].…”
Section: Introductionmentioning
confidence: 99%